In vitro gene expression profile of bovine peripheral blood mononuclear cells in early Mycobacterium bovis infection - CHENG, YAFEN (Exp Ther Med, 2015)
The intracellular parasite Mycobacterium bovis (M. bovis) causes tuberculosis in cattle and humans. Understanding the interactions between M. bovis and host cells is essential in developing tools for the prevention, detection, and treatment of M. bovis infection. Gene expression profiles provide a large amount of information regarding the molecular mechanisms underlying these interactions. The present study analyzed changes in gene expression in bovine peripheral blood mononuclear cells (PBMCs) at 0, 4 and 24 h following exposure to M. bovis. Using bovine whole-genome microarrays, a total of 420 genes were identified that exhibited significant alterations in expression (≥2-fold). Significantly enriched genes were identified using the Kyoto Encyclopedia of Genes and Genomes database, of which the highest differentially expressed genes were associated with the immune system, signal transduction, endocytosis, cellular transport, inflammation, and apoptosis. Of the genes associated with the immune system, 84.85% displayed downregulation. These findings support the view that M. bovis inhibits signaling pathways of antimycobacterial host defense in bovine PBMCs. These in vitro data demonstrated that molecular alterations underlying the pathogenesis of tuberculosis begin early, during the initial 24 h following M. bovis infection.